Effect of protein fraction of Carica papaya L. leaves on the expressions of p53 and Bcl-2 in breast cancer cells line - Rumiyati .; Sismindari .; Ariyani . (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2006)
Carica papaya L. leave was known containing Ribosome-inactivating proteins (RIPs), which demonstrated to have an in vitro cytotoxic effect on cancer cell lines. This researh examined the effect of protein fraction containing RIPs isolated from Carica papaya L. on the expressions of p53 and Bcl-2, regulator proteins on apoptosis process, in breast cancer cell lines (T47D).RIPs from Carica papaya L. leaves were isolated by amonium sulfat precipitation. This fraction was analyzed by the activity of cleaving supercoiled double stranded DNA, in order to identify the presence of RIP. The active fraction was then tested of the citotoxic activity on breast cancer cell lines followed by analysing the expressions of p53 and bcl2 using immunohistochemistry technique.The results indicated that the protein fraction possessed cytotoxic activity in breast cancer cell line with the IC50 of 2.8 mg/mL. The expression level of p53 was increased by 59.4%, while Bcl-2 protein was decreased by 63%. These results suggested that this protein could induce apoptotic process.Key words : protein fraction, Carica papaya L. , expression of p53 and Bcl-2